Diversity and bio-indicators of tropical urban lichens in Jakarta, Indonesia - RIZHAL HENDI RISTANTO; MUHAMMAD ALHADY; RIFKY ADI SAPUTRA; ERICKA DARMAWAN (Society for Indonesian Biodiversity, 2025)
Abstract. Ristanto RH, Alhady M, Saputra RA, Darmawan E. 2025. Diversity and bio-indicators of tropical urban lichens in Jakarta, Indonesia. Biodiversitas 26: 5505-5514. Lichens are highly sensitive to air quality changes, making them effective bioindicators for assessing pollution in urban areas. This study analyzed the diversity, dominance, and evenness indices of lichens across urban forests in Jakarta, Indonesia. Sampling was conducted using the cruise and purposive methods, with each administrative city represented by one urban forest park. A total of 18 lichen species were identified, dominated by Bacidia viridifarinosa (35,257 individuals). Penjaringan City Forest showed the highest diversity (H’: 1.295), dominance (D: 0.667), and evenness (J’: 0.723), indicating relatively good air quality. In contrast, Pondok Kelapa (H’: 0.142; D: 0.062; J’: 0.205) and Srengseng Sawah (H’: 0.251; D: 0.071; J’: 0.140) were dominated by a single crustose species tolerant to pollution. Although Gelora Bung Karno Forest had more species, one foliose species dominated, suggesting an imbalance. Overall, lichen distribution patterns reflected high air pollution levels in Jakarta, influenced by temperature, pH, and light intensity. These findings confirm that lichen community compositions can reflect air quality gradients and serve as an effective and economic tool to monitor the environment in urban areas. Air pollution can have a serious impact on public health, requiring public education and implementation of curriculum in schools through environmental education.